THE VOICE AND THE SONG FRO A GLOBAL AND INTERDISCIPLINARY APPROACH INPRIMARY EDUCATION - Garcia, Iciar Nadal; Casanova, Belen Lopez (European Scientific Journal, ESJ, 2014)
Through the voice and song we can find the right tools to work in an interdisciplinary, globalized and changing learning environment. This approach is about creating new strategies for working with different competencies required in the acquisition of knowledge, promoting active and collaborative methodologies and in consideration of diversity. During this process students involved Teacher Education and teachers from different knowledge areas of the Faculty of Education at the University of Zaragoza (Spain). The song will apply its power to stimulate emotions, develop sensitivity, memory and imagination. Our principal objective is to use the voice and the song as an interdisciplinary tool for students taking a Master Degree in Primary Education (6-12 years) in the acquisition of different competencies. The results take into consideration the potential lack of a musical background that students may have, an emphasis has been placed on the selection of the material used and the change in attitude of participants during the process, in assessing the experience positively.